2009
DOI: 10.1186/1746-160x-5-13
|View full text |Cite
|
Sign up to set email alerts
|

A new biphasic osteoinductive calcium composite material with a negative Zeta potential for bone augmentation

Abstract: The aim of the present study was to analyze the osteogenic potential of a biphasic calcium composite material (BCC) with a negative surface charge for maxillary sinus floor augmentation. In a 61 year old patient, the BCC material was used in a bilateral sinus floor augmentation procedure. Six months postoperative, a bone sample was taken from the augmented regions before two titanium implants were inserted at each side. We analyzed bone neoformation by histology, bone density by computed tomography, and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 26 publications
1
67
1
1
Order By: Relevance
“…Therefore, the adhesion of osteoblasts to the implant is to a large extent determined by the electrical properties of the implant surface. Accordingly, many studies in the past indicated that increased negative surface potential of titanium implants promotes osteoblast adhesion and consequently, to new bone formation [29,31,32]. It it shown in this work that depletion and water ordering near the charged surface of a metal implant locally decrease the relative permittivity.…”
Section: Langevin-bikerman Stern (Lbs) Model For Finite-sized Ionsmentioning
confidence: 65%
See 2 more Smart Citations
“…Therefore, the adhesion of osteoblasts to the implant is to a large extent determined by the electrical properties of the implant surface. Accordingly, many studies in the past indicated that increased negative surface potential of titanium implants promotes osteoblast adhesion and consequently, to new bone formation [29,31,32]. It it shown in this work that depletion and water ordering near the charged surface of a metal implant locally decrease the relative permittivity.…”
Section: Langevin-bikerman Stern (Lbs) Model For Finite-sized Ionsmentioning
confidence: 65%
“…It it shown in this work that depletion and water ordering near the charged surface of a metal implant locally decrease the relative permittivity. The electric field strength and the magnitude of the negative electric potential in the close vicinity of the implant surface, due to this effect, are substantially increased which is of a crucial importance for the improved adhesion of cells to the metal surface [28,29,31,32]. Accordingly, it has been shown recently that the topography of a nanostructured implant surface is a decisive factor for surface cell adhesion and growth [33][34][35].…”
Section: Langevin-bikerman Stern (Lbs) Model For Finite-sized Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the osteoblast cell membrane makes a nonspecific contact due to electrostatic forces, 15 followed by a second step where specific binding involving integrin assembly into focal contacts takes place. 16,23,24 Since osteoblasts are negatively charged, 25 they are electrostatically repelled by the negatively charged titanium surface as long as some other attractive forces are not present in the system. Recently, a possible mechanism of osteoblast adhesion to the implant surface was proposed on the assumption that positively charged proteins 25,26 or proteins with positively charged tips, ie, a quadrupolar internal charge distribution 15 attached to the negatively charged implant surface, serve as a substrate for the subsequent attachment of negatively charged osteoblasts.…”
Section: Adhesion Of Proteins To a Titanium Surfacementioning
confidence: 99%
“…At pH 7.4, ALN results in positive zeta potentials, while RIS results in negative ones as a function of concentration, most likely due to the differing nitrogen charges/species among the two bisphosphonates. (1) Cells may sense and react to this potential, (46)(47)(48)(49)(50)(51)(52)(53) thus it is plausible that the different affinities and zeta-potentials influence osteoblastic function differently, quantitatively and/or qualitatively.…”
Section: Discussionmentioning
confidence: 99%